HUL and Conservation of the Historic City of Kulangsu: A Scoping Case. (2nd October 2018) - Yan, Sun
ABSTRACT: The Recommendation on the Historic Urban Landscape (2011) adopted on the 36th UNESCO General Conference stressed that Historic Urban Landscape (HUL) was not a new type of world heritage, but an innovative method in urban heritage conservation. The paper discusses current efforts for applying the HUL Approach in the case of urban heritage conservation of Kulangsu in China, a project for World Heritage nomination in 2017. For Kulangsu, the World Heritage nomination provides an opportunity to rethink its values and characteristics in the global perspective. The HUL Approach also provides a new perspective for identifying the heritage components of the site, and thus changes the conservation system and strategies in order to improve the built environment, the quality of social life, and to enhance the interaction between the community and the site. The paper will introduce the outstanding universal values of the site, the identification of the elements of urban heritage, the understanding of its integrity, the practical challenges and conservation strategies.